2022
DOI: 10.1088/2053-1591/ac58e9
|View full text |Cite
|
Sign up to set email alerts
|

Primary Si refinement and eutectic Si modification in Al-20Si via P-Ce addition

Abstract: Enhancing the mechanical properties of hypereutectic Al-Si alloys by refining the primary and eutectic Si morphology is very challenging. In this study, the refinement mechanism of primary and eutectic Si morphologies via the simultaneous addition of P-Ce into the Al-20Si alloy was studied. Microstructural analysis revealed that the primary and eutectic Si morphologies were significantly refined, which increased the tensile strength. Furthermore, the addition of Ce, up to 0.6 wt%, can result in the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Figure 10(c) shows the diffraction spot (SAED) at one point on the gray strip-like phase. After calibration, it is concluded that the gray strip-like phase is the Al 8 Si 6 Mg 3 Fe phase [19,28], and the crystal band axis is [−1210]. Combined with the Mapping results in figures 10(d)-(g), it is found that Al, Si, Mg, and Fe are abundantly enriched in the gray elongated phase, which verifies that the elongated phase is Al 8 Si 6 Mg 3 Fe.…”
Section: Dsc Analysis Of Experimental Alloysmentioning
confidence: 54%
See 1 more Smart Citation
“…Figure 10(c) shows the diffraction spot (SAED) at one point on the gray strip-like phase. After calibration, it is concluded that the gray strip-like phase is the Al 8 Si 6 Mg 3 Fe phase [19,28], and the crystal band axis is [−1210]. Combined with the Mapping results in figures 10(d)-(g), it is found that Al, Si, Mg, and Fe are abundantly enriched in the gray elongated phase, which verifies that the elongated phase is Al 8 Si 6 Mg 3 Fe.…”
Section: Dsc Analysis Of Experimental Alloysmentioning
confidence: 54%
“…Adding trace amounts of Y [11], Mn, Mo [12,13], La and Zr [14,15] to hypoeutectic Al-Si alloys can change the morphology of the alloy, reduce the size of eutectic Si, and refine α-Al dendrites. Among the various available rare earth elements, Ce has become a good candidate element for microalloying of Al-Si casting alloys in terms of cost and demand in the metallurgical market [16][17][18][19][20][21]. Cai Yuzhou [22] et al added Ce in the Al-7Si-0.35Mg alloy, two phases of Ce-23Al-22Si and Al-17Ce-12Ti-2Si-2Mg were formed in the alloy, and the eutectic Si was well obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth element addition to the Al-Si binary system has long been an area of investigation. Still, the mechanism behind the micro-alloying of rare earth element modifications, namely refinement of Si phases and coupled zone transitions, has not been fully understood [41]. It can be speculated that, since the heat history within the melt pool is similar, the undercooling amounts caused by micro-alloying elements are different.…”
Section: Silicon Fiber Refinement Within the Melt Poolmentioning
confidence: 99%